Arabic Vocabulary And Its Cultural Influences On The Colloquial Tamil Language: Special Reference To South Tamil Nadu India/ المفردات العربية وتأثيراتها الثقافية في اللغة التاميلية العامية : جنوب ولاية تاميل نادو في الهند أنموذجا - Kadir K J, Mohideen Abdul; Mohideen, H.L.M. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Language is vital for exchanging opinions and ideas, expressing feelings, and fulfilling daily needs. Arabic stands out among other languages due to its various advantages and features. Tamil Nadu, one of the states in India, is known as the historical frame of the Dravidian civilization, one of India's oldest. It is situated in the southernmost part of Asia. Tamil Nadu's residents speak Tamil, an ancient and expressive language celebrated for its rich literature and esteemed position among Indian languages. Tamil Nadu's global prominence stems from its historical oceanic and commercial connections. Centuries ago, the state actively traded with China, Babylonia, Rome, the Levant, the Turks, and, notably, the Arabs. These trade interactions facilitated vigorous import-export activities and improved cultural exchange and integration among diverse peoples. This study focuses on the influence of the Arabic language on Tamil, particularly in contemporary usage, where many Arabic words have been integrated into Tamil vocabulary. This research emphasizes the everyday use of Arabic terms, especially in fields such as law, exemplified by terms like amal, asal, bark, taraf, waterish, wakeel, and wayeetha, etc. It examines the linguistic and cultural similarities and shared usage of words between these two distinct languages. The methodology adopted is qualitative. The primary data was collected through personal interviews and original texts. Secondary data were obtained from related books, and scholarly works and data were analyzed. This study concluded that Arabic influence in colloquial Tamil, especially in southern Tamil Nadu, needs more extensive research. The persistent Arabic influence on Tamil civilization and cultural practices is frequently mistaken for indigenous Tamil elements in academic and administrative contexts. Arabic words used in Tamil have their roots and origins, emphasizing their originality in the Arabic language rather than being borrowed from Tamil.